Major data gaps and recommendations in monitoring regulations of activities in EU marine protected areas - Juliette Aminian-Biquet; Jennifer Sletten; Timothé Vincent; Margherita Pieraccini; Betty Queffelec; Anastasiya Laznya; Natașa Vaidianu; Joachim Claudet; Juliette Young; Barbara Horta e Costa (npj Ocean Sustainability)
Abstract Marine Protected Areas (MPAs) play a central role in maritime policies, but there are no comprehensive analyses of regulations in EU MPAs. Using publicly available data on EU MPAs’ regulations for nine activities, we first show that MPA and MSP databases display significant gaps in data comprehensiveness. The regulation of each activity was known in 40% or less of the MPA area (whether allowed, prohibited, or restricted), except for fishing activities (70% of MPA area), albeit with limited detail. Fishing, mining, or dredging/dumping activities were allowed in half of MPA area. Only mining was reported as prohibited in at least 10% of the MPA area. We discuss gaps in MPA regulatory data in light of existing reporting requirements, insufficient connection between various actors and data sources, and challenges in translating legal information into actionable indicators. We provide recommendations for future initiatives to improve the collection and standardization for environmental policies.